Ecm29-mediated proteasomal distribution modulates excitatory GABA responses in the developing brain - Lee, Min (J Cell Biol, 2020)
Neuronal GABAergic responses switch from excitatory to inhibitory at an early postnatal period in rodents. The timing of this switch is controlled by intracellular Cl(−) concentrations, but factors determining local levels of cation-chloride cotransporters remain elusive. Here, we report that local abundance of the chloride importer NKCC1 and timely emergence of GABAergic inhibition are modulated by proteasome distribution, which is mediated through interactions of proteasomes with the adaptor Ecm29 and the axon initial segment (AIS) scaffold protein ankyrin G. Mechanistically, both the Ecm29 N-terminal domain and an intact AIS structure are required for transport and tethering of proteasomes in the AIS region. In mice, Ecm29 knockout (KO) in neurons increases the density of NKCC1 protein in the AIS region, a change that positively correlates with a delay in the GABAergic response switch. Phenotypically, Ecm29 KO mice showed increased firing frequency of action potentials at early postnatal ages and were hypersusceptible to chemically induced convulsive seizures. Finally, Ecm29 KO neurons exhibited accelerated AIS developmental positioning, reflecting a perturbed AIS morphological plastic response to hyperexcitability arising from proteasome inhibition, a phenotype rescued by ectopic Ecm29 expression or NKCC1 inhibition. Together, our findings support the idea that neuronal maturation requires regulation of proteasomal distribution controlled by Ecm29.